2022
DOI: 10.1002/tox.23718
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective efficacy of the bacterial metabolite, prodigiosin, against aluminium chloride‐induced neurochemical alternations associated with Alzheimer's disease murine model: Involvement of Nrf2/HO‐1/NF‐κB signaling

Abstract: Prodigiosin (PDG) is a bacterial metabolite with numerous biological and pharmaceutical properties. Exposure to aluminium is considered a root etiological factor in the pathological progress of Alzheimer's disease (AD). Here, in this investigation, we explored the neuroprotective potential of PDG against aluminium chloride (AlCl 3 )mediated AD-like neurological alterations in rats. For this purpose, rats were gavaged either AlCl 3 (100 mg/kg), PDG (300 mg/kg), or both for 42 days. As a result of the analyzes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Tetrahydrocurcumin inhibits cell cycle arrest and microglia apoptosis via the Ras/ERK signaling pathway 65 . Prodigiosin attenuates oxidative injury, neuroinflammation, and apoptosis in hippocampal tissue through the Nrf2/HO-1/NF-κB signaling pathway 66 . Lactobacillus plantarum DP189 exerts neuroprotective effects by inhibiting tau protein hyperphosphorylation via PI3K/Akt/GSK-3β 67 .…”
Section: Discussionmentioning
confidence: 99%
“…Tetrahydrocurcumin inhibits cell cycle arrest and microglia apoptosis via the Ras/ERK signaling pathway 65 . Prodigiosin attenuates oxidative injury, neuroinflammation, and apoptosis in hippocampal tissue through the Nrf2/HO-1/NF-κB signaling pathway 66 . Lactobacillus plantarum DP189 exerts neuroprotective effects by inhibiting tau protein hyperphosphorylation via PI3K/Akt/GSK-3β 67 .…”
Section: Discussionmentioning
confidence: 99%
“… 52–54 Upon being activated, NF-κB moves to the nucleus and phosphorylates its p65 subunit, this triggers elevation of pro-inflammatory cytokines eg, IL-1β. 55 , 56 Wang et al 57 reported that MM and cyanuric acid co-treatment increased the phosphorylation level of NF-κB as well as the mRNA expression of NLRP3 inflammasome in the kidney in rats. Increased NF-κB expression levels in hepatocytes of MM-exposed rats was observed which indicated that inflammatory reaction mediated by MM exposure.…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with our histopathological results, which elucidate inflammatory cell infiltration, and with our immunohistochemistry findings that exhibited increased expression of NF-κB in liver tissue. Intriguingly, NF-κB, a marker of the inflammatory process, is a transcription factor concerned with proinflammatory mediator regulation, chemokine expression, and cytokine activation [ 40 , 41 , 42 , 43 , 44 ]. In addition, the knockdown of Nrf2 can enhance NF-κB expression and cytokine production [ 45 ].…”
Section: Discussionmentioning
confidence: 99%